La ‘pre-historia’ de la Historia de la Monja Alférez… contada por ella misma, de Catalina de Erauso (Siglo XVII) (El Hilo de la Fabula, 2022)
The present work focuses on the pre-history or extra-textual life of Catalina de Erauso prior to her flight from the convent of San Sebastián, as her travel narrative enables a writing space that stresses and unmasks links between ethnicity- the Basque-, race- the Spanish-, and education- conventual. Her only work, that of Historia de la Monja Alférez… told by herself, is born from the authorial will of Catalina who dialogues through memory with her past in which life, background and experiences in the convent left her traces on a personal, corporal and literary level.
Keywords: Catalina de Erauso; pre-textual history; conventual education